Assessing cognitive biases induced by acute formalin or hotplate treatment: an animal study using affective bias test - Zhang, Yu-Han; Lin, Jie-Xuan; Wang, Ning; Wang, Jin-Yan; Luo, Fei (Frontiers in Behavioral Neuroscience, 2024)
Pain, a universal and burdensome condition, influences numerous individuals worldwide. It encompasses sensory, emotional, and cognitive facets, with recent research placing a heightened emphasis on comprehending pain's impact on emotion and cognition. Cognitive bias, which encompasses attentional bias, interpretation bias, and memory bias, signifies the presence of cognitive distortions influenced by emotional factors. It has gained significant prominence in pain-related research. Human studies have shown that individuals experiencing pain exhibit cognitive bias. Similarly, animal studies have demonstrated cognitive bias in pain-induced states across various species and disease models. In this study, we aimed to investigate the memory bias displayed by rats experiencing acute pain, using the affective bias test (ABT) as a tool and administering either hotplate or formalin to induce acute pain. Our data showed that rats demonstrated a significant preference for the control treatment-related substrate over the substrate associated with formalin treatment (p < 0.001), an indication of the prominent memory bias stimulated by acute formalin injections. However, when exposed to substrates related to hotplate treatment and control treatment, the acute pain induced by the hotplate treatment failed to generate a statistically significant choice bias in rats (p = 0.674). Our study demonstrates that the negative emotions associated with acute pain can be reflected by memory bias in ABT, at least for formalin-induced acute pain. This finding will augment our comprehension of the emotional and cognitive aspects of acute pain.